Kajian Literatur Potensi Integrasi Game-Based Learning untuk Meningkatkan Literasi Digital Siswa Sekolah Dasar - Muhammad Nur Abdullah (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2026)
The rapid development of digital technology requires elementary school students to possess adequate digital literacy skills from an early age. However, previous studies indicate that increased access to technology is not always accompanied by the ability to use it critically, ethically, and productively. One learning approach considered capable of supporting digital literacy development is Game-Based Learning (GBL). This study aims to analyze the potential integration of GBL in enhancing elementary school students’ digital literacy through a Systematic Literature Review (SLR). The review adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, including identification, screening, eligibility assessment, and inclusion stages. Literature was collected from articles published between 2020 and 2025 through Google Scholar and SINTA-indexed educational journals. Of the 142 articles identified, 38 met the inclusion criteria and were analyzed using thematic analysis. The findings reveal that GBL is strongly grounded in constructivism, learning by doing, state of flow, and the development of Higher Order Thinking Skills (HOTS). The reviewed studies consistently report positive impacts of GBL on learning motivation, conceptual understanding, critical thinking, collaboration, and students’ digital literacy. Furthermore, the characteristics of GBL are aligned with the principles of the Merdeka Curriculum. Nevertheless, its implementation still faces challenges related to technological infrastructure, teacher competence, and educational ecosystem support. Therefore, optimizing GBL requires improved instructional design, continuous teacher professional development, and adequate educational support systems. The findings indicate that GBL has strong potential as an effective learning approach for fostering digital literacy among elementary school students.